The new kid on the block : poems - Prelutsky, Jack.; Stevenson, James, 1929- (New York : Greenwillow Books, 1984)
Humorous poems about such strange creatures and people as Baloney Belly Billy and the Gloopy Gloopers.
Includes index.
Children's Catalog (Wilson)
School Library Journal
Horn Book Magazine
3.7
3-6
Keywords: Children's poetry, American; Humorous poetry; American poetry; Humorous poetry; American poetry